Atenção em saúde mental: a prática do enfermeiro e do médico no programa saúde da família em Caucaia-Ce - Nascimento, Adail Afrânio Marcelino do (2004)
This study for objective to analyze the nursing and doctor practice on the Family Health program (PSF) as the attencion in mental health, in the perspective of the Psychiatric Reform. It is as descriptive study, with qualitave nature, accomplished with seven nurses and five doctors of a municipal discrict of Ceará. The data were collected by semi- structured glimpses and free observation, in the period from May to July of 2003. After being contained in categories and sub-categories, the results show that the nurses and doctors of PSF develop their action in logic of the programming in heath, accomplishing the foreseen protocol. We observed that they feel a lot of difficulty for working appropriately with the demands of the attended community’s mental health, condition that become evident through some answers of the group, such as: the confused way that they define what is mental health; the use of the guiding as one of the main action strategies; inability recognition in the management of the community’s demands; ignorance and low use of the management of the community’s resources to act in preventive actions; restricted use of a sensitive listening and of the interpersonal reiationship; recognition of trainig lack, insecurity and absence of professional experience in working with those demands. Finally, it was possible to understand that the actions of mental health developed by the researched group are guided by the practice of the traditional psychiatry, in which the medicating and the guiding are the choice Instruments. This condition goes against that what the Psychiatric Reform